Perception Analysis of Desktop and Mobile Service Website - Rizqiyatul Khoiriyah (ComTech: Computer, Mathematics and Engineering Applications, 2016)
The research was conducted as a qualitative study of the website to deeper explore and examine the analysis of user perception of desktop and mobile website services. This research reviewed about user perception of desktop and mobile service website used by using qualitative methods adapted to WebQual and User Experience approach. This qualitative research refered to the theoretical reference written by Creswell (2014). The expected outcome is to know the user perceptions of the available services and information in the website along with the possibility of desktop and mobile gap arising from differences in the two services. These results can be used as a service model on the website of the user experience.